2015
DOI: 10.1186/s12885-015-1944-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel human leiomyoma tissue derived matrix for cell culture studies

Abstract: BackgroundThe composition of the matrix molecules is important in in vitro cell culture experiments of e.g. human cancer invasion and vessel formation. Currently, the mouse Engelbreth-Holm-Swarm (EHS) sarcoma -derived products, such as Matrigel®, are the most commonly used tumor microenvironment (TME) mimicking matrices for experimental studies. However, since Matrigel® is non-human in origin, its molecular composition does not accurately simulate human TME. We have previously described a solid 3D organotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 48 publications
4
108
0
Order By: Relevance
“…CD95 L plays an important tumor supportive role in both breast tumor cells and endothelial cells controlling the angiogenic process. CD95 L (soluble), or Fas-L is an effector regulator of endothelial cell survival in recently formed endothelial cells related with the cytokines identified in our screen, including IL-8 and VEGF [42, 43]. Using an antibody specific to the CD95 L soluble form, we observed that the levels of CD95 L in the flow cytometry analysis were negligible in the FBS and PPP supplemented control breast tumors cells (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…CD95 L plays an important tumor supportive role in both breast tumor cells and endothelial cells controlling the angiogenic process. CD95 L (soluble), or Fas-L is an effector regulator of endothelial cell survival in recently formed endothelial cells related with the cytokines identified in our screen, including IL-8 and VEGF [42, 43]. Using an antibody specific to the CD95 L soluble form, we observed that the levels of CD95 L in the flow cytometry analysis were negligible in the FBS and PPP supplemented control breast tumors cells (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…Engelbreth-Holm-Swarm (EHS) mouse sarcoma cells are the prevailing substrates in the majority of in vitro cell invasion studies [1]. We have recently described a novel protein extract made of human uterus leiomyoma tissue and demonstrated that it is superior to Matrigel in in vitro cancer and angiogenesis studies [2]. However, such protein mixtures lack the complex 3D architecture which also influences proteolytic actions during cell invasion [3].…”
Section: Extracellular Matrix (Ecm) Protein Mixtures Of Non-human Orimentioning
confidence: 99%
“…These collagen‐containing matrices may well be lacking collagen fiber structures required for birefringence . Matrigel and Myogel are mechanically and chemically processed preparations . As for the cell clusters in Matrigel, inadequate alignment of the newly synthesized immature collagen fibers is not causing the positive signal similar to mature collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
“…For the liquid biomaterials in the 3D‐cryo well inserts we placed cells in Myogel (a human leiomyoma‐derived matrix suspension in media) and in cell culture media. The preparation of the biomaterial Myogel has been described in detail in another publication . The Ethics Committee of Oulu University Hospital approved our use of the myoma tissue obtained from a patient's uterus leiomyoma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation